1999
DOI: 10.1152/jappl.1999.87.6.2032
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance spectroscopy, exercise, and oxidative stress: an ascorbic acid intervention study

Abstract: Oxygen free radicals are highly reactive species that are produced in increased quantities during strenuous exercise and can damage critical biological targets such as membrane phospholipids. The present study examined the effect of acute ascorbic acid supplementation on exercise-induced free radical production in healthy subjects. Results demonstrate increases in the intensity of the alpha-phenyl-tert-butylnitrone adduct (0.05 +/- 0.02 preexercise vs. 0.19 +/- 0.03 postexercise, P = 0.002, arbitrary units) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
0
11

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 18 publications
(18 reference statements)
4
107
0
11
Order By: Relevance
“…There was, however, a mild attenuation of free radical species and LOOH following ingestion of 1 g of ascorbic acid, demonstrating that ascorbic acid does not completely abolish PBN adduct production. These findings are in general agreement with the work of Ashton et al [9] showing a decrease in EPR signal amplitude after supplementation with 1 g ascorbic acid in ten healthy male volunteers. We have previously observed an attenuation of EPR signals following the addition of ascorbic acid to the in vitro oxidation of α-linolenic acid, postulating that ascorbic acid has the ability to scavenge free radicals generated from a lipid environment [30].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…There was, however, a mild attenuation of free radical species and LOOH following ingestion of 1 g of ascorbic acid, demonstrating that ascorbic acid does not completely abolish PBN adduct production. These findings are in general agreement with the work of Ashton et al [9] showing a decrease in EPR signal amplitude after supplementation with 1 g ascorbic acid in ten healthy male volunteers. We have previously observed an attenuation of EPR signals following the addition of ascorbic acid to the in vitro oxidation of α-linolenic acid, postulating that ascorbic acid has the ability to scavenge free radicals generated from a lipid environment [30].…”
Section: Discussionsupporting
confidence: 93%
“…The period of 2 h was chosen specifically to allow the venous concentration of ascorbate to rise from baseline to >100 μmol/l to near cell saturation, based on previous work by Ashton et al [9]. The participants were given a small volume of water in order to ensure complete ingestion.…”
Section: Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22] There are no studies that have been conducted until now about molecular effects of short-term low-intensity exercise training, such as ROS and NO production, especially in patients hospitalized with AMI. There are no reports about this kind of study and our study is the first reporting it.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Production of ROS in well-trained patients was lower than in sedentary patients, meanwhile, NO was higher. [19][20][21][22][23] It also had been shown that short-term low-intensity exercise training within 5 days could rapidly elevate internal antioxidants in the diaphragm muscle of rats, accompanied by a reduction in contraction-induced lipid peroxidation or ROS production, but generated high NO consistently.…”
mentioning
confidence: 87%